1996
DOI: 10.1291/hypres.19.57
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium Channel Blocker Controversy.

Abstract: A major controversy about the safety of calcium channel blockers (CCBs) has arisen since the publication of a case-control study showing that hypertensives who suffered an acute myocardial infarction (MI) were more likely than hypertensives who had not had an MI to be taking one of these (short-acting) agents than other antihypertensive agents. This study was accompanied by a republication of older studies showing that large doses of short-acting nifedipine given to post-MI patients increased their mortality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…However, because DPCs are potent agents and may sometimes cause an excessive decrease in blood pressure, there is a question as to whether this reduction in blood pressure aggravates blood flow to the target organs of hypertension; i.e., coronary, vertebral and renal flows. Also, because DPCs are known to induce reflectional sympathetic activation (9)(10)(11), this may have an adverse effect on coronary circulation, and some studies (12)(13)(14) have reported that the incidence of myocardial infarction is higher when nifedipine, a short-acting DPC, is were studied (5 men and 4 women; mean age SD, 59 5 years). All patients had complained of chest pain on effort and/or at rest and seven patients showed positive ST segment depression on treadmill exercise testing.…”
Section: Introductionmentioning
confidence: 99%
“…However, because DPCs are potent agents and may sometimes cause an excessive decrease in blood pressure, there is a question as to whether this reduction in blood pressure aggravates blood flow to the target organs of hypertension; i.e., coronary, vertebral and renal flows. Also, because DPCs are known to induce reflectional sympathetic activation (9)(10)(11), this may have an adverse effect on coronary circulation, and some studies (12)(13)(14) have reported that the incidence of myocardial infarction is higher when nifedipine, a short-acting DPC, is were studied (5 men and 4 women; mean age SD, 59 5 years). All patients had complained of chest pain on effort and/or at rest and seven patients showed positive ST segment depression on treadmill exercise testing.…”
Section: Introductionmentioning
confidence: 99%
“…3). These findings indicate that an acute severe drop in blood pressure may increase reflex tachycardia, worsen cardiac loading, and subsequently increase mortality [Kaplan, 1996;Cain et al, 1999]. Because of this high mortality, humoral signaling and PKC-E translocation data from rats treated with 20 mg kg À1 day À1 of nifedipine were not compared with similar data from rats in the other treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant prehypertensive changes take place with respect to PRA [Miyamori et al, 1990], Ang II, and ANP [Tikkanen et al, 1987], as well as with respect to increased ET-1 gene expression [Touyz et al, 1998], elevated sympathetic drive, and a distorted baroreflex response [Weinstock et al, 1984]. Adrenergic antagonist and calcium channel blocking agents have antihypertensive properties that not only inhibit catecholamine-induced activities, but also retard humoral signaling during long-term therapy [Kaplan, 1996;Tsoporis and Leenen, 1988]. We theorized that a pharmacologic agent with triple blocking activities on a/b-adrenergic receptors and calcium channels would regulate DOCA-saltmediated responses.…”
Section: Introductionmentioning
confidence: 99%
“…A major controversy has risen over the safety of CCBs as I have described in a previous article for Drugs of Today's Timely Topics in Medicine (8). Since that publication, additional evidence has documented both the probable hazards of short-acting CCBs (never indicated for the treatment of hypertension) and the safety of long-acting CCBs (approved for the treatment of hypertension).…”
Section: The Issue Of Ccb Safetymentioning
confidence: 99%